The “IAG-Switch”—A Key Controlling Element in Decapod Crustacean Sex Differentiation - Levy, Tom; Sagi, Amir (Frontiers in Endocrinology, 2020)
The androgenic gland (AG) – a unique crustacean endocrine organ that secretes factors such as the insulin-like androgenic gland (IAG) hormone – is a key player in crustacean sex differentiation processes. IAG expression induces masculinization, while the absence of the AG or a deficiency in IAG expression results in feminization. Therefore, by virtue of its universal role as a master regulator of crustacean sexual development, the IAG hormone may be regarded as the sexual 'IAG-switch.' The switch functions within an endocrine axis governed by neuropeptides secreted from the eyestalks, and interacts downstream with specific insulin receptors at its target organs. In recent years, IAG hormones have been found – and sequenced – in dozens of decapod crustacean species, including crabs, prawns, crayfish and shrimps, bearing different types of reproductive strategies—from gonochorism, through hermaphroditism and intersexuality, to parthenogenesis. The IAG-switch has thus been the focus of efforts to manipulate sex developmental processes in crustaceans. Most sex manipulations were performed using AG ablation or knock-down of the IAG gene in males in order to sex reverse them into 'neo-females,' or using AG implantation/injecting AG extracts or cells into females to produce 'neo-males.' These manipulations have highlighted the striking crustacean sexual plasticity in different species and have permitted the manifestation of either maleness or femaleness without altering the genotype of the animals. Furthermore, these sex manipulations have not only facilitated fundamental studies of crustacean sexual mechanisms, but have also enabled the development of the first IAG-switch-based monosex population biotechnologies, primarily for aquaculture but also for pest control. Here, we review the crustacean IAG-switch, a unique crustacean endocrine mechanism, from the early discoveries of the AG and the IAG hormone to recent IAG-switch-based manipulations. Moreover, we discuss this unique early pancrustacean insulin-based sexual differentiation control mechanism in contrast to the extensively studied mechanisms in vertebrates, which are based on sex steroids.